Sang Hyang Dedari: Balinese Women in Schizoanalytic Approach - Dewi, Saraswati (Jurnal Perempuan, 2015)
Sang Hyang Dedari Dance in religious ceremonies is not only aimed vertically to Sang Hyang Widhi, but also bearing horizontal objectives, to sustain stable structure in Bali society. This study aims to describe the layers of the society, so it can be understood critically what is meant by women of Bali—that the multicultural discourse, indigenous women celebrate the customs and traditions as an act against the root of patriarchy. Yet there is always a need to reexamine the roots. Root is not absolute, and a single tone, but rhizomes that question the hegemony of the hierarchy in winning gender equality against patriarchal subordination.